Factors Associated with The Incidence of Infection in Tracheostomy Stoma at Mohammad Hoesin Hospital - Lisa Apri Yanti; Nelly Oktriyani; Erial Bahar (HM Publisher, 2021)
Introduction: Tracheostomy is a surgery to open the trachea to allow air to enter the airway. Tracheostomy cannot be separated from possible complications. Tracheostomy stoma infection is one of the complications of post-tracheostomy that occurs due to the activity of several bacteria. Many factros can cause the incidence of tracheostomy stoma infection. Objective: The aim of this study is to determine the factors associated with the incidence of tracheostomy stoma infection. Methods: Observational study with cross-sectional design. Data collection was carried out using medical record data on 71 subjects who underwent tracheostomy tube replacement from july 2019 to November 2020. Results: From 71 subjects, it was found that the subjects who had tracheostomy stoma infection were 54.9%. The results of bivariate analysis showed that age (p=0.031), comorbidities (p=0.009), the type of tracheostomy tube (p=0.015), the use of antiseptic in tracheostomy dressing (p=0.020), tracheostomy tube care (p=0.013), and the interval of changing the tracheostomy tube (p=0.041) are the significant factors. The results of multivariate analysis showed that tracheostomy tube care and the interval of changing the tracheostomy tube had a significant effect on tracheostomy stoma infection. Tracheostomy tube care has a risk of 9.362 times to experience infection with CI95%(1.535-57.086) and the interval of changing the tracheostomy tube has a risk of 10.669 with CI95% (1.074-105.985). Conclusion: There is a significant relationship between age, comorbidities, type of tracheostomy tube, the use of antiseptic in tracheosotmy dressing, tracheosotmy tube care, and interval of changing the tracheostomy tube with the incidence of tracheostomy stoma infection.